Bi2O3-Bi2S3 heterogeneous catalytic material, preparation method thereof and application of Bi2O3-Bi2S3 heterogeneous catalytic material in electrocatalytic CO2 reduction electrode

Through the preparation and application of Bi2O3-Bi2S3 heterogeneous catalytic materials, the problems of insufficient formic acid selectivity and CO2 reduction reaction activity at multiple potentials and smaller potentials are solved, and high efficiency is achieved under smaller overpotentials The CO2 is reduced to formic acid, meeting the needs of industrialization.

CN119194501AActive Publication Date: 2024-12-27HEILONGJIANG UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411369925.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-27
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

The existing Bi-based materials are difficult to effectively improve the selectivity of formic acid and CO2 reduction reaction activity under multiple potentials and smaller potentials, and cannot meet the industrialized CO2 reduction formic acid requirements.

Method used

By using the preparation method of Bi2O3-Bi2S3 heterogeneous catalytic material, Bi2O3-Bi2S3 heterogeneous catalytic material was prepared by dissolving thiourea in anhydrous ethanol and reacting with bismuth salt, adding glycerol for hydrothermal treatment, and then preparing Bi2O3-Bi2S3 heterogeneous catalytic material with no Water ethanol and 5% Nafion solution were mixed, and ultrasonic dispersed on hydrophobic carbon paper to form an electrocatalytic CO2 reduction electrode.

Benefits of technology

It significantly improves the formic acid selectivity and CO2 reduction reaction activity of the catalyst, enhances the adsorption capacity and kinetics of the catalyst, and realizes more efficient CO2 reduction to formic acid at a smaller overpotential, broadening the electrochemical window for electrocatalytic CO2 reduction. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194501A_ABST
    Figure CN119194501A_ABST
Patent Text Reader

Abstract

The invention relates to a Bi2O3-Bi2S3 heterogeneous catalytic material, a preparation method thereof and application of the Bi2O3-Bi2S3 heterogeneous catalytic material in an electrocatalytic CO2 reduction electrode. The invention belongs to the field of electrocatalysts. The invention solves the problem that the Bi-series material can only show high formic acid selectivity under one or more potentials, and provides a high-activity catalytic material which still shows high formic acid selectivity and CO2 reduction reaction under multiple potentials and small potentials. According to the method, the Bi2O3-Bi2S3 catalytic material can be obtained at a time, and the ratio of Bi2O3 to Bi2S3 is controllable, so that the Bi2O3-Bi2S3 catalytic material prepared by the method not only has high formic acid selectivity of Bi2O3, but also has high electro-catalysis CO2 reduction reaction activity of Bi2S3, the capability of reducing CO2 into formic acid by electro-catalysis of a catalyst is greatly improved, and a new way is provided for realizing efficient conversion of CO2 industrially.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of electrocatalysts, and specifically relates to a Bi2O3-Bi2S3 heterogeneous catalytic material and a preparation method thereof and application in an electrocatalytic CO2 reduction electrode. Background Art

[0002] The advancement of industrialization has accelerated social progress and improved the quality of human life, but it has also made environmental pollution increasingly severe to a certain extent. Since the Industrial Revolution, excessive consumption of fossil fuels has caused a large amount of CO2 emissions, leading to many environmental problems including the greenhouse effect. In order to actively respond to global climate change, the use of environmentally friendly materials, reducing CO2 emissions, and strengthening CO2 recycling and reuse are the main means to solve environmental pollution such as the greenhouse effect. Electrocatalytic CO2 reduction technology driven by green energy (solar energy, wind energy, hydropower, tidal energy, etc.) can convert CO2, a rich "carbon source" in nature, into high-value-added chemicals such as CO, formic acid, methane, methanol and ethylene under mild conditions. It is a promising "negative carbon economy" model that can not only alleviate the environmental problems caused by carbon emissions, but also realize the resource utilization of CO2. Formic acid is an important chemical raw material, widely used in many industries such as pesticides, dyes and pharmaceuticals. In the past few decades, people have been committed to developing catalytic materials with excellent performance (such as Bi, Sn, In, etc.). Among them, bismuth (Bi)-based catalysts have become ideal electrocatalysts for the reduction of CO2 to formic acid due to their high formic acid selectivity, high catalytic activity, long-term stability, low cost and environmental friendliness.

[0003] However, current Bi-based materials can only show high formic acid Faradaic efficiency (FE>90%) at one or several potentials, especially at small overpotentials, which makes it difficult to meet the industrial demand for formic acid reduction. Therefore, it is urgent to develop more high-performance Bi-based electrocatalysts that can improve formic acid selectivity and CO2 reduction reaction activity at multiple potentials and small potentials to meet industrial needs. Summary of the invention

[0004] In view of the above problems, the present invention provides a Bi2O3-Bi2S3 heterogeneous catalytic material and a preparation method thereof, aiming to solve the problem of improving formic acid selectivity and CO2 reduction reaction activity at multiple potentials and lower potentials.

[0005] The technical solution of the present invention is as follows:

[0006] One of the purposes of the present invention is to provide a method for preparing a Bi2O3-Bi2S3 heterogeneous catalytic material, the method comprising:

[0007] S1: dissolving thiourea in anhydrous ethanol to obtain solution 1;

[0008] S2: adding bismuth salt to solution 1 to obtain solution 2;

[0009] S3: Add propylene glycol dropwise into solution 2 and heat in a hydrothermal kettle to obtain a Bi2O3-Bi2S3 heterogeneous catalytic material.

[0010] It is further defined that the concentration of thiourea in solution 1 is 0.01-0.2 mol L -1 .

[0011] It is further defined that the concentration of bismuth salt in solution 2 is 0.05-0.3 mol L -1 The bismuth salt is bismuth nitrate pentahydrate, bismuth chloride, bismuth sulfate or bismuth acetate.

[0012] It is further defined that the reaction temperature in S3 is 80-180°C.

[0013] It is further defined that the reaction time in S3 is 12-24 hours.

[0014] It is further defined that the volume ratio of glycerol to anhydrous ethanol is 1:1-5.

[0015] The second object of the present invention is to provide a Bi2O3-Bi2S3 heterogeneous catalytic material prepared by the above-mentioned preparation method.

[0016] The third object of the present invention is to provide an electrocatalytic CO2 reduction electrode, which is prepared by the above-mentioned Bi2O3-Bi2S3 heterogeneous catalytic material, anhydrous ethanol, 5% perfluorosulfonic acid polymer (Nafion) solution and hydrophobic carbon paper.

[0017] A fourth object of the present invention is to provide a method for preparing an electrocatalytic CO2 reduction electrode, the method comprising:

[0018] The Bi2O3-Bi2S3 heterogeneous catalytic material, anhydrous ethanol and 5% Nafion solution were mixed and ultrasonically dispersed, and then uniformly coated on hydrophobic carbon paper and dried to obtain an electrocatalytic CO2 reduction electrode.

[0019] A fifth object of the present invention is to provide an application of the above-mentioned electrocatalytic CO2 reduction electrode in the preparation of formic acid.

[0020] Compared with the prior art, the specific advantages of the present invention are as follows:

[0021] (1) The method provided by the present invention can obtain a Bi2O3-Bi2S3 heterogeneous catalytic material at one time. The material has both the high formic acid selectivity of Bi2O3 and the high electrocatalytic CO2 reduction reaction activity of Bi2S3, thereby greatly improving the catalyst's ability to electrocatalyze CO2 reduction to formic acid, providing a new way to achieve efficient CO2 conversion.

[0022] (2) The Bi2O3-Bi2S3 heterogeneous catalytic material provided by the present invention improves the local electronic structure of the material, increases the specific surface area of ​​the material, strengthens the adsorption capacity between the catalyst and CO2, increases the kinetics of the electrocatalytic CO2 reduction reaction, improves the catalytic ability of the catalyst, and thus improves the activity and selectivity of the catalyst.

[0023] (3) Compared with Bi2O3 or Bi2S3 alone, the Bi2O3-Bi2S3 heterogeneous catalytic material provided by the present invention has a better ability to reduce CO2 to formic acid at a smaller overpotential.

[0024] (4) In the present invention, when preparing Bi2O3-Bi2S3 heterogeneous catalytic materials, as the amount of thiourea added increases, the content of Bi2S3 in the heterogeneous structure will increase. Based on this property, Bi2O3-Bi2S3 heterogeneous catalytic materials with different ratios of Bi2O3 and Bi2S3 can be prepared by controlling the amount of thiourea added. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 a is the transmission electron microscope image of Example 1, Figure 1 b is the HRTEM image of Example 1, Figure 1 c is the distribution diagram of Bi, O, and S elements in Example 1;

[0026] Figure 2 The XRD patterns of Example 1, Example 4, Example 5, Comparative Example 1 and Comparative Example 2 are shown in FIG.

[0027] Figure 3 a is the nitrogen adsorption-desorption curve of Example 1, Comparative Example 1 and Comparative Example 2, Figure 3 b is the CO2 adsorption curve of Example 1, Comparative Example 1 and Comparative Example 2;

[0028] Figure 4 a is the Faraday efficiency diagram of the electrocatalytic CO2 reduction reaction product of Example 3, Figure 4 b Faraday efficiency diagram of the electrocatalytic CO2 reduction reaction product of Comparative Example 5, Figure 4 c is the Faraday efficiency diagram of the electrocatalytic CO2 reduction reaction product of Comparative Example 6;

[0029] Figure 5 a is the current density diagram of Example 3, Comparative Example 5 and Comparative Example 6, Figure 5 b is the local current density diagram of formic acid in Example 3, Comparative Example 5 and Comparative Example 6;

[0030] Figure 6 It is the Tafel slope of Example 3, Comparative Example 5 and Comparative Example 6. DETAILED DESCRIPTION

[0031] The present invention provides a method for preparing a Bi2O3-Bi2S3 heterogeneous catalytic material, which is achieved by the following steps:

[0032] Dissolve thiourea in anhydrous ethanol and stir for 10-30 minutes to obtain solution 1, add bismuth salt, stir for 10-60 minutes to obtain solution 2, add propylene glycol dropwise, and after uniform dispersion, transfer the obtained solution to a hydrothermal autoclave for reaction, then cool to room temperature, repeat centrifugal washing three times with anhydrous ethanol, and dry to obtain Bi2O3-Bi2S3 heterogeneous catalytic material.

[0033] Preferably, the bismuth salt is one of bismuth nitrate pentahydrate, bismuth chloride, bismuth sulfate or bismuth acetate, and most preferably is bismuth nitrate pentahydrate.

[0034] Preferably, the concentration of thiourea in solution 1 is 0.01 to 0.2 mol L -1 Most preferably, the concentration of thiourea is 0.05 mol L -1 .

[0035] Preferably, the concentration of bismuth salt in solution 2 is 0.05-0.3 mol L -1 .

[0036] Preferably, the ratio of glycerol to anhydrous ethanol is 1:1-5, and most preferably, the ratio of glycerol to anhydrous ethanol is 1:3.

[0037] Preferably, the oven temperature is 80-180°C, and the reaction time is 12-24h. Most preferably, the oven temperature is 150°C, and the reaction time is 16h.

[0038] The present invention provides a method for preparing an electrocatalytic CO2 reduction electrode, which is implemented by the following steps:

[0039] The Bi2O3-Bi2S3 heterogeneous catalytic material, ethanol and 5% Nafion solution were mixed and ultrasonically dispersed, and then the mixed solution was evenly coated on hydrophobic carbon paper and dried to obtain an electrocatalytic CO2 reduction electrode. The loading amount of the catalytic material was 1 mg cm -2 .

[0040] Preferably, the ultrasonic time is 20-60 min, most preferably 30 min.

[0041] The present invention provides a method for preparing formic acid by using an electrocatalytic CO2 reduction electrode, which is implemented by the following steps:

[0042] A standard three-electrode system is used, with the electrocatalytic CO2 reduction electrode as the working electrode, to carry out electrocatalytic CO2 reduction in an electrolytic cell to prepare formic acid. The electrolytic cell is a liquid flow cell, the cathode cell and the anode cell are separated by a proton exchange membrane, the CO2 flow rate is 10-40sccm, and the electrolyte flow rate is 1-10mL / min.

[0043] Preferably, iridium oxide is the counter electrode, the silver / silver chloride electrode is the reference electrode, and the potassium hydroxide solution is the electrolyte.

[0044] Preferably, the potassium hydroxide concentration is 1 mol L -1 .

[0045] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0046] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0047] Embodiment 1:

[0048] Preparation of Bi2O3-Bi2S3 heterogeneous catalytic materials, the specific steps are:

[0049] Dissolve 3 mmol of thiourea in 60 mL of anhydrous ethanol, stir for 10 min, then add 9 mmol of bismuth nitrate pentahydrate, stir for 30 min, then add 20 mL of propylene glycol dropwise, disperse evenly and transfer to a hydrothermal autoclave, react in an oven at 150 °C for 15 h, cool to room temperature, repeat centrifugal washing three times with anhydrous ethanol, and dry in an oven at 60 °C to obtain a Bi2O3-Bi2S3 heterogeneous catalytic material.

[0050] Embodiment 2:

[0051] Preparation of electrocatalytic CO2 reduction electrode, the specific steps are:

[0052] 8 mg of the Bi2O3-Bi2S3 heterogeneous catalytic material prepared in Example 1, 10 mL of ethanol and 0.02 mL of 5% Nafion solution were mixed and ultrasonically dispersed for 30 min, and then the mixed solution was evenly coated on a hydrophobic carbon paper and dried to obtain an electrocatalytic CO2 reduction electrode. The loading amount of the catalytic material was 1 mg cm -2 .

[0053] Embodiment 3:

[0054] The electrocatalytic CO2 reduction electrode is used to prepare formic acid. The specific steps are as follows:

[0055] The electrocatalytic CO2 reduction electrode of Example 2 was used as the working electrode, iridium oxide was used as the counter electrode, and the silver / silver chloride electrode was used as the reference electrode. -1 Potassium hydroxide solution was used as the electrolyte, the CO2 flow rate was 26 sccm, and the electrolyte flow rate of the cathode and anode was 5 mL / min. The electrocatalytic CO2 reduction reaction was carried out in the electrolytic cell. During the electrocatalytic CO2 reduction reaction test, the chronoamperometric test was carried out at different potentials, and the applied voltage range was -0.3 to -1.0 V. RHE .

[0056] Embodiment 4:

[0057] Preparation of Bi2O3-Bi2S3-0.5 heterogeneous catalytic material, the specific steps are:

[0058] Dissolve 1.5 mmol of thiourea in 60 mL of anhydrous ethanol, stir for 10 min, then add 9 mmol of bismuth nitrate pentahydrate, stir for 30 min, then add 20 mL of propylene glycol dropwise, disperse evenly and transfer to a hydrothermal autoclave, react in an oven at 150 °C for 15 h, cool to room temperature, repeat centrifugal washing three times with anhydrous ethanol, and dry in an oven at 60 °C to obtain a Bi2O3-Bi2S3-0.5 heterogeneous catalytic material.

[0059] Embodiment 5:

[0060] Preparation of Bi2O3-Bi2S3-2 heterogeneous catalytic material, the specific steps are:

[0061] Dissolve 6 mmol of thiourea in 60 mL of anhydrous ethanol, stir for 10 min, then add 9 mmol of bismuth nitrate pentahydrate, stir for 30 min, then add 20 mL of propylene glycol dropwise, disperse evenly and transfer to a hydrothermal autoclave, react in an oven at 150 °C for 15 h, cool to room temperature, repeat centrifugal washing three times with anhydrous ethanol, and dry in an oven at 60 °C to obtain a Bi2O3-Bi2S3-2 heterogeneous catalytic material.

[0062] Comparative Example 1:

[0063] The preparation of Bi2O3, the specific steps are:

[0064] Dissolve 9 mmol of bismuth nitrate pentahydrate in 60 mL of anhydrous ethanol, stir for 30 min, add 20 mL of propylene glycol dropwise, transfer to a hydrothermal autoclave after uniform dispersion, react in an oven at 150°C for 15 h, cool to room temperature, repeat centrifugal washing with anhydrous ethanol three times, and dry in an oven at 60°C to obtain Bi2O3.

[0065] Comparative Example 2:

[0066] The preparation of Bi2S3, the specific steps are:

[0067] Dissolve 45 mmol of thiourea in 60 mL of anhydrous ethanol, stir for 10 min, then add 3 mmol of bismuth nitrate pentahydrate, stir for 30 min, add 20 mL of propylene glycol dropwise, disperse evenly, transfer to a hydrothermal autoclave, react in an oven at 150°C for 15 h, cool to room temperature, repeat centrifugal washing with anhydrous ethanol three times, and dry in an oven at 60°C to obtain Bi2S3.

[0068] Comparative Example 3:

[0069] Preparation of electrocatalytic CO2 reduction electrode: The preparation method is the same as Example 2, except that the catalyst material used is Bi2O3 prepared in Comparative Example 1.

[0070] Comparative Example 4:

[0071] Preparation of electrocatalytic CO2 reduction electrode: The preparation method is the same as Example 2, except that the catalyst material used is Bi2S3 prepared in Comparative Example 2.

[0072] Comparative Example 5:

[0073] The electrocatalytic CO2 reduction electrode is used to prepare formic acid. The preparation method is the same as that in Example 3, except that the working electrode is the Bi2O3 electrode prepared in Comparative Example 3.

[0074] Comparative Example 6:

[0075] The electrocatalytic CO2 reduction electrode is used to prepare formic acid. The preparation method is the same as that in Example 3, except that the working electrode is the Bi2S3 electrode prepared in Comparative Example 4.

[0076] Figure 1 a is a transmission electron microscope image of Example 1, from Figure 1 In a, it can be seen that Bi2O3-Bi2S3 is a spherical structure with a rough surface and a diameter of about 2.2 μm. Figure 1 b Example 1 Two types of lattice fringes can be observed in the HRTEM image, one with a 0.20nm interplanar spacing corresponding to the (220) crystal plane of Bi2O3, and the other with a 0.35nm interplanar spacing corresponding to the (111) crystal plane of Bi2S3. Therefore, the close combination of Bi2O3 and Bi2S3 in Bi2O3-Bi2S3 promotes the formation of a large number of Bi2O3 (220)-Bi2S3 (111) staggered crystal planes. This heterogeneous crystal plane that can produce a synergistic effect in the electrocatalytic process is expected to promote the electrocatalytic CO2 reduction reaction. Figure 1In c, it can be observed that Bi, O, and S elements are evenly distributed in the entire Bi2O3-Bi2S3 heterogeneous catalytic material, which shows that Bi2S3 and Bi2O3 have been evenly compounded into Bi2O3-Bi2S3 heterogeneous catalytic material.

[0077] Figure 2 The XRD diagrams of Example 1, Example 4, Example 5, Comparative Example 1 and Comparative Example 2 show that the crystallinity of Bi2O3 is relatively low, and its XRD diffraction peaks match the standard diffraction peaks of Bi2O3 (JCPDS 52-1007) of the cubic system. The crystallinity of Bi2S3 is relatively high, and its XRD diffraction peaks match the standard diffraction peaks of Bi2S3 (JCPDS 84-0279) of the orthorhombic system. The XRD diagram of Bi2O3-Bi2S3 is mainly composed of the characteristic diffraction peaks (110), (111), (122), (130), (131) of Bi2S3 and the characteristic diffraction peak (101) of Bi2O3. Compared with the XRD characteristic peaks of pure phase Bi2S3, the XRD characteristic peaks of Bi2S3 in Bi2O3-Bi2S3 move to a larger angle, indicating that part of O is doped into the lattice of Bi2S3. The XRD peak intensity of the Bi2O3 (101) crystal plane in Bi2O3-Bi2S3 is significantly greater than that of pure Bi2O3, indicating that the catalyst material is formed with Bi2S3 with high crystallinity, which increases the crystallinity of Bi2O3. In addition, in the process of preparing Bi2O3-Bi2S3 heterogeneous catalytic materials, with the increase of thiourea addition, the XRD diffraction peak intensity of Bi2S3 in the heterogeneous structure gradually increases, indicating that the content of Bi2S3 gradually increases. Therefore, this experimental scheme can achieve the regulation of the ratio of Bi2O3 and Bi2S3 in the Bi2O3-Bi2S3 heterogeneous material by adjusting the amount of thiourea added.

[0078] Figure 3 a is the nitrogen adsorption-desorption curve of Example 1, Comparative Example 1 and Comparative Example 2. As shown in the figure, the specific surface areas of Bi2O3-Bi2S3, Bi2O3 and Bi2S3 are 39.4, 16.1 and 9.2 m 2 g -1 , Bi2O3-Bi2S3 has a larger specific surface area than the other two catalytic materials, and is expected to expose more active sites in the electrocatalytic CO2 reduction reaction, thereby improving the reaction performance. Figure 3b is the CO2 adsorption curve of Example 1, Comparative Example 1, and Comparative Example 2. As shown in the figure, the CO2 absorption volume of all catalysts increases with the increase of the relative pressure of the gas. Since the alkalinity of Bi2O3 is greater than that of Bi2S3, the adsorption amount of CO2 by Bi2O3 is greater than that by Bi2S3 under the same relative pressure. After the two are combined, the adsorption amount of CO2 by the obtained Bi2O3-Bi2S3 is significantly improved, thereby promoting CO2 molecules to be more easily adsorbed on the catalyst, thereby increasing the mass transfer rate on the electrode surface, and finally promoting the subsequent electrocatalytic CO2 reduction process.

[0079] Figure 4 Graph showing the Faraday efficiency of the electrocatalytic CO2 reduction reaction products of Example 3, Comparative Example 5 and Comparative Example 6. Figure 4 As shown in a, Bi2O3-Bi2S3 is at -0.3~-1.0V RHE The product of the electrocatalytic CO2 reduction reaction within the range is mainly formic acid (HCOOH), accompanied by a small amount of by-products (H2, CO). The starting potential of the electrocatalytic CO2 reduction to formic acid is -0.3V RHE , the overpotential is 0.1V. As the applied potential increases from -0.3V RHE Change to -1.0V RHE , the formic acid Faradaic efficiency (FE 甲酸 ) increases first and then decreases, and at -0.6V RHE The maximum value reaches 99.5% at -0.4~-1.0V RHE In this wide potential window (600mV), Bi2O3-Bi2S3 甲酸 Maintained above 90%. Figure 4 As shown in b, the electrocatalytic CO2 reduction performance of Bi2O3 is weaker than that of Bi2O3-Bi2S3, and its formic acid starting potential is -0.4V RHE , the overpotential is 0.2V. As the applied potential increases from -0.4V RHE Change to -1.0V RHE , FE of Bi2O3 甲酸 It also shows a trend of increasing first and then decreasing, and at -0.8V RHE The maximum value reaches 98.8% at -0.6~-1.0V RHE In this potential window (400mV), Bi2O3 converts FE 甲酸 Maintained above 90%. Figure 4 As shown in c, the electrocatalytic CO2 reduction reaction performance of Bi2S3 is poor at -0.3 and -0.4V RHE Under the potential, only hydrogen evolution reaction occurred, at -0.5~-1.0VRHE Potential range FE H2 Both are higher than Bi2O3-Bi2S3 and Bi2O3. The starting potential of formic acid is -0.5V RHE (overpotential is 0.3V), at this potential, its FE 甲酸 It is only 56.1%. As the applied potential increases from -0.5V RHE Change to -1.0V RHE , FE of Bi2S3 甲酸 It also shows a trend of increasing first and then decreasing, and at -0.9V RHE The maximum value is 97.1% at -0.9 to -1.0V. RHE Within this potential window (200mV), Bi2S3 will FE 甲酸 It is obvious that the Bi2O3-Bi2S3 heterogeneous catalytic material obtained by compounding Bi2O3 and Bi2S3 can significantly improve the selectivity of formic acid in the electrocatalytic CO2 reduction reaction. 甲酸 The maximum value can be increased to 99.5% (-0.6V RHE potential), is the same applied potential, Bi2O3 FE 甲酸 1.08 times the maximum value, Bi2S3 FE 甲酸 In addition, the overpotential of electrocatalytic CO2 reduction to formic acid was reduced to 0.1 V. RHE , lower than Bi2O3 and Bi2S3. And FE 甲酸 >90% of the electrochemical window is extended to -0.4~-1.0V RHE This wider potential window.

[0080] Figure 5 The current density and the local current density of formic acid in Example 3, Comparative Example 5 and Comparative Example 6 are shown in FIG. Figure 5 As shown in a, the total current density of the three catalysts under the same conditions is in the following order: Bi2S3>Bi2O3-Bi2S3>Bi2O3. RHE The total current density of the Bi2O3-Bi2S3 heterogeneous catalytic material is 122.7 mA cm -2 , which is significantly higher than the total current density of Bi2O3 under the same conditions (75.3 mA cm -2 ), but is lower than the total current density of Bi2S3 under the same conditions (140.3 mA cm -2 ).like Figure 5 As shown in b, compared with Bi2O3 and Bi2S3, the composite of the two into Bi2O3-Bi2S3 heterogeneous catalytic material can significantly increase the local current density of formic acid. RHEThe local current density of formic acid in Bi2O3-Bi2S3 is 122.1 mA cm -2 , which is 1.77 times that of Bi2O3 (68.8 mA cm -2 ), which is 1.24 times that of Bi2S3 (98.2 mA cm -2 ).

[0081] Figure 6 The Tafel slopes of Example 3, Comparative Example 5 and Comparative Example 6 are shown in the figure. As shown in the figure, the Tafel slope can be reduced by compounding Bi2O3 and Bi2S3 (Bi2O3-Bi2S3: 127.03 mV dec -1 <Bi2O3:140.98mV dec -1 <Bi2S3:156.92mV dec -1 ), therefore, among the three catalysts of Bi2O3-Bi2S3, Bi2O3, and Bi2S3, Bi2O3-Bi2S3 can exhibit faster reaction kinetics in the process of CO2 reduction to HCOOH, thereby promoting the electrocatalytic CO2 reduction reaction.

[0082] The present invention is at -0.6V RHE Under potential, FE of Bi2O3-Bi2S3 甲酸 The local current density of formic acid increased to 122.1 mA cm -2 It is 1.77 times that of Bi2O3 and 1.24 times that of Bi2S3 under the same conditions; when the formic acid starting potential of Bi2O3-Bi2S3 is -0.3V RHE When the potential is low, FE 甲酸 Still greater than 90%, under the same conditions, Bi2O3 and Bi2S3 do not produce formic acid.

[0083] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a Bi2O3-Bi2S3 heterogeneous catalytic material, characterized in that: The method: S1: dissolving thiourea in anhydrous ethanol to obtain solution 1; S2: adding bismuth salt to solution 1 to obtain solution 2; S3: Add propylene glycol dropwise into solution 2 and heat in a hydrothermal kettle to obtain a Bi2O3-Bi2S3 heterogeneous catalytic material.

2. The method according to claim 1, characterized in that: The concentration of thiourea in solution 1 is 0.01-0.2 mol L -1 .

3. The method according to claim 1, characterized in that: The concentration of bismuth salt in solution 2 is 0.05-0.3 mol L -1 The bismuth salt is bismuth nitrate pentahydrate, bismuth chloride, bismuth sulfate or bismuth acetate.

4. The method according to claim 1, characterized in that The reaction temperature in S3 is 80-180°C.

5. The method according to claim 1, characterized in that: The reaction time in S3 is 12-24h.

6. The method according to claim 1, characterized in that The volume ratio of glycerol to anhydrous ethanol is 1:1-5.

7. A Bi2O3-Bi2S3 heterogeneous catalytic material, characterized in that: The method is prepared by any one of claims 1 to 6.

8. An electrocatalytic CO2 reduction electrode, characterized in that: The reduction electrode is prepared from the Bi2O3-Bi2S3 heterogeneous catalytic material according to claim 7, anhydrous ethanol, 5% Nafion solution and hydrophobic carbon paper.

9. The method for preparing the electrocatalytic CO2 reduction electrode according to claim 8, characterized in that: The method: The Bi2O3-Bi2S3 heterogeneous catalytic material according to claim 7, anhydrous ethanol and 5% Nafion solution are mixed and ultrasonically dispersed, and then uniformly coated on hydrophobic carbon paper and dried to obtain an electrocatalytic CO2 reduction electrode.

10. Use of the electrocatalytic CO2 reduction electrode according to claim 8 in the preparation of formic acid.

Citation Information

Patent Citations

  • Bismuth-based catalyst for electrocatalytic CO2 reduction to form formic acid and preparation method and application thereof

    CN109518222A

  • Bi2O2SO4 catalyst, preparation method and application of Bi2O2SO4 catalyst in electrocatalytic reduction of CO2

    CN114808004A

  • Method for producing formic acid by coupling anode methanol oxidation and cathode carbon dioxide reduction

    CN115652342A

  • Bismuth sulfide-carbon nanomaterial as well as preparation method and application thereof

    CN115896857A

  • Gas-phase diffusion electrode for producing formic acid by reducing CO2 through electro-catalysis, preparation method and application

    CN116676615A